Mechanistic studies on the photodynamic effect induced by a dicationic fullerene C60 derivative on Escherichia coli and Candida albicans cells - Milanesio, María Elisa (2013)
The photodynamic mechanism of action induced by N,N-dimethyl-2-(4′-N,N,N-trimethylaminophenyl)fulleropyrrolidinium iodide (DTC602+) was investigated on Candida albicans and Escherichia coli cells. First, photogeneration of superoxide anion radical by DTC602+ in the presence of NADH was detected using nitro blue tetrazolium method in reverse micelles. In C. albicans suspensions, 10 μM DTC602+ was an effective photosensitizer, producing a ∼5 log decrease of cell survival when the cultures were irradiated for 30 min with visible light. Also, C. albicans cells growth was not detected in the presence of 10 μM DTC602+ and irradiation. Photodynamic mechanism investigations were compared in both C. albicans and E. coli cells. Studies under anoxic conditions indicated that oxygen was required for the photodynamic inactivation of these microorganisms. The photocytotoxicity induced by DTC602+ was similar in D2O than in water cell suspensions. Furthermore, photoinactivation of microbial cells was negligible in the presence of azide ion, while the addition of mannitol produced a photoprotective effect on the cellular survival. These results indicate that DTC602+ has potential as agent to the photodynamic inactivation of microbial cells. Also, the photocytotoxicity activity induced by this cationic fullerene derivative can involve the intermediacy of both superoxide anion radical and singlet molecular oxygen.